2020
DOI: 10.36630/jasft_19059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Technological and Organoleptic Quality of Meat of Muscovy Duck from South-Benin

Abstract: Muscovy duck is the most reared palmiped species in Benin. However, no scientific data exist on its meat quality. The objective of this study was to evaluate the technological and organoleptic qualities of meat from this species reared in South-Benin. Data on technological and organoleptic qualities were collected on 40 ducks. Females' breast muscle pH was lower than that of males during the 48-h post-mortem (p<0.001). The breast and the thigh muscles pH and temperature and the water holding capacity varied si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[ 9 ]. A progressive increase in pH with age was also observed in Muscovy ducks [ 22 ]. The differences between these latter results and those of this study could be explained by differences in the age periods considered and in the genetic types.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…[ 9 ]. A progressive increase in pH with age was also observed in Muscovy ducks [ 22 ]. The differences between these latter results and those of this study could be explained by differences in the age periods considered and in the genetic types.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies observed that luminance and redness index decreased significantly with age when they studied 20-, 24-, and 28-week-old cockerels [ 10 ]. In Muscovy ducks, it was also observed that ducks older than 10 months had darker muscles than younger ducks [ 22 ]. The red index and hue of the wishbone and brightness of the thigh and tail assembly of females were lower than those of males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation